Smart and real-time door lock system for an elderly user based on face recognition - Rezki Saputra; Nico Surantha (Bulletin of Electrical Engineering and Informatics, 2021)
Many sophisticated smart door lock systems have been made. Still, most of them required the user to use an additional device such as a smartphone, tag, smartcard, or accessing some user interfaces, which is complicated to use for inexperienced elderly. This condition creates a gap between the elderly and technology which makes it difficult for the elderly to accept and use the technology. In this paper, we proposed a smart and real-time door lock system for an elderly user based on local binary pattern histogram as a face recognition algorithm with modular system architecture design. The novelty in our proposed system design, it does not require any additional device, it does not use any user interface, and the least user participation by automating the processes. All the user needs to do just walk toward the door and stand in front of it and the door will automatically unlock and locked back after the user enters the house and close the door. The system resulted in an accuracy of 98%, with an average processing time is 1.449 seconds for the entire process. Additional advantages, the system is designed with a modular approach that makes it flexible and scalable for further development.